2022
DOI: 10.51867/ajernet3.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Human Resource Practices and Employee Retention in a Private Commercial Bank in Nairobi County, Kenya

Abstract: Employees are always regarded as an organization's biggest asset because the workforce is a major component of every business. Organizations cannot deliver business results, satisfy organizational goals, or reach their financial targets without personnel. The majority of corporations understand how crucial human resources are to their businesses' success. It is impossible to overstate the importance of employing excellent strategic human resource management techniques, particularly when dealing with a dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The findings were that redesigning the job is meaningfully and inversely correlated to task execution at the initial implementation stage. The finding from the research study was that work satisfaction is notably related to job performance (Kiragu & Marwa, 2022). They concluded that the organization should promote employee satisfaction during job redesign to improve performance.…”
Section: Ho2 There Is No Relationship Between Secondary Occupational ...mentioning
confidence: 95%
“…The findings were that redesigning the job is meaningfully and inversely correlated to task execution at the initial implementation stage. The finding from the research study was that work satisfaction is notably related to job performance (Kiragu & Marwa, 2022). They concluded that the organization should promote employee satisfaction during job redesign to improve performance.…”
Section: Ho2 There Is No Relationship Between Secondary Occupational ...mentioning
confidence: 95%
“…It provides the foundation for strategic reviews, which are conducted following studies of the organizational context and practices to make judgments on strategic plans for the creation of general or focused HR strategies. SHRM includes both setting strategic priorities and making strategic decisions (Kiragu & Marwa, 2022). Nowadays, modern companies view SHRM as a new paradigm for managing human capital at work (Waiganjo et al, 2012).…”
Section: Impact Of Shrm Practices On Employee Retention: Shrestha And...mentioning
confidence: 99%
“…Organizations in the business world today must understand the value of human resources and how to use them to run successful businesses. A prosperous company may have the greatest advantage in terms of technology, depth of capital, market position, etc., but it will be useless without an experienced workforce to handle all of its various jobs and responsibilities (Kiragu & Marwa, 2022). Moreover, it cannot progress to accomplish any of its corporate or organizational objectives (Mwami, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In procurement perspective, studies have addressed the effect of e-procurement on customer satisfaction in a number of ways. For example, Kiragu (2012), reported that the use of e-procurement enables an organization to manage whole life cost of materials hence making an organization achieve value for money in the procurement process. An organization can create value to the customers by providing reliable services and demonstrating high level of responsiveness that guarantee timely services to customers.…”
Section: Impact Of E-procurement On Customer Satisfactionmentioning
confidence: 99%